ESP-102, a Combined Herbal Extract of Angelica gigas, Saururus chinensis, and Schisandra chinensis, Changes Synaptic Plasticity and Attenuates Scopolamine-Induced Memory Impairment in Rat Hippocampus Tissue - Kim, Hyun-Bum (Evid Based Complement Alternat Med, 2016)
ESP-102, an extract from Angelica gigas, Saururus chinensis, and Schisandra chinensis, has been used as herbal medicine and dietary supplement in Korea. Despite the numerous bioactivities in vitro and in vivo studies, its effects on neuronal networks remain elusive. To address the neuronal effect, we examined synaptic plasticity in organotypic hippocampal slice culture with multielectrode array. Our results showed an increase in excitatory postsynaptic potential (EPSP), indicating the induction of long-term potentiation (LTP), in the presence of ESP-102. In addition, the neuroprotective effect of ESP-102 was also tested by application of scopolamine to the hippocampal slice. Interestingly, ESP-102 competitively antagonized the preventative LTP effect induced by scopolamine. The scopolamine-induced reduction in brain-derived neurotrophic factor (BDNF) and GluR-2 expression was also rescued by ESP-102. In terms of mode of action, ESP-102 appears to act on the presynaptic region independent of AMPA/NMDA receptors. Based on these findings, ESP-102 can be suggested as a novel herbal ingredient with memory enhancing as well as neuroprotective effects.